Grant Deed
In consideration of $10.00, receipt of which is acknowledge, Carl E. Pedersen and Agathe Pedersen, husband and wife, do hereby grant to Tressa Grinolds, a widow, the real property in the County of Ventura, State of California described as: Lot 20 of Kadota Fig Farms, Subdivision No. 4, as per map recorded in the office of the County Recorder of Ventura County, in Book 18 of Maps at Pages 48 and 49.